A New View of Bone Loss in Phenylketonuria. (2nd October 2021) - Dobrowolski, Steven F.; Tourkova, Irina L.; Sudano, Cayla R.; Larrouture, Quitterie C; Blair, Harry C.
ABSTRACT: Osteopenia is common in phenylalanine hydroxylase deficient phenylketonuria (PKU). PKU is managed by limiting dietary phenylalanine. Osteopenia in PKU might reflect a therapeutic diet, with reduced bone forming materials. However, osteopenia occurs in patients who never received dietary therapy or following short-term therapy. Humans and animal studies find no correlation between bone loss, plasma hyperphenylalaninemia, bone formation, and resorption markers. Work in the Pah enu2 mouse recently showed a mesenchymal stem cell (MSC) developmental defect in the osteoblast pathway. Specifically, Pah enu2 MSCs are affected by energy dysregulation and oxidative stress. In PKU, MSCs oximetry and respirometry show mitochondrial respiratory-chain complex 1 deficit and over-representation of superoxide, producing reactive oxygen species affecting mitochondrial function. Similar mechanisms are involved in aging bone and other rare defects including alkaptonuria and homocysteinemia. Novel interventions to support energy and reduce oxidative stress may restore bone formation PKU patients, and in metabolic diseases with related mechanisms.